Organisasi Koperasi dan Ekonomi Koperasi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Koperatives are a form of people-based economic organization that play a strategic role in improving community welfare and strengthening the national economy. However, many cooperatives still face organizational and managerial challenges that limit their economic performance. This study aims to analyze the relationship between cooperative organizational structures, governance mechanisms, and the economic performance of cooperatives in the context of modern economic transformation. A qualitative descriptive approach was employed to gain an in-depth understanding of organizational practices within cooperatives. Data were collected through in-depth interviews, participatory observation, and document analysis involving cooperative managers, members, and supervisors selected purposively. The findings indicate that cooperatives with clear organizational structures, professional management, transparent governance, and active member participation tend to demonstrate better economic performance and sustainability. Conversely, weak organizational arrangements and low member involvement are associated with stagnation in cooperative economic activities. These results highlight that organizational quality is a key determinant of cooperative success, not merely financial factors. The study implies that strengthening cooperative governance, improving human resource capacity, and enhancing member participation are essential strategies to increase the competitiveness of cooperatives in the digital economy era. This research contributes to the development of cooperative economic theory and provides practical recommendations for cooperative managers and policymakers.